Studies on luminous Vibrio harveyi isolated from Penaeus monodon larvae reared in hatcheries in Andamans - Shome, Rajeshwari; Shome, B R; Soundararajan, R (Indian Journal of Fisheries, 2011)
A small prawn hatchery unit, established recently at the Central Agricultural Research Institute, Andaman, to produce prawn seed mainly of tiger prawn, Penaeus monodon, encountered the problem of luminous bacteria (LB) in rearing tanks, attacking at larval developmental stages. Detailed bacteriological investigation revealed high bacterial counts in intake source of sea water, filter bed filtered sea water, maturation and larval rearing tanks and low bacterial counts in slow sand filtered -UV- radiation treated - again slow sand filtered sea water. The LB could be isolated from intake sea water using Dunlop selective media suggesting that the main source of infection was from intake sea water. The LB were also isolated from filter bed sea water, maturation tanks and nauplii stages of larval development. Four LB isolates have been identified by morphological, cultural and various biochemical tests as luminous Vibrio harveyi. They were found to be sensitive to seven antibiotics and resistant against 11 others when tested by in vitro antibiotic disc diffusion test. However, the sensitive antibiotics, when used either as prophylactic or therapeutic agents, did not have appreciable effect on the LB population. The non-effectiveness of the antibiotics might be related to the tendency of V. harveyi forming biofilms in rearing tanks. The processing of intake sea water by filtration followed by UV treatment and again refiltration was found to be the effective way to reduce the bacterial counts and thus, the luminous V. harveyi load in the hatchery unit.